Seaside Tourism in Romania - Marian Ionel (Ovidius University Annals: Economic Sciences Series, 2020)
Seaside tourism is an important form of tourism that involves capitalizing on natural resources (water, sand and sun). The capitalization from the tourist point of view of these natural resources implies the existence of the technical and material base materialized in accommodation units, in dining units and in leisure and entertainment units, but also the existence of the labor force. In Romania, seaside tourism has a central place in the tourist activity because in this area is found the largest accommodation capacity. After 1990, seaside tourism in Romania has experienced a downward trend due to factors such as: low quality of services, inadequate management of natural resources, the existence of a low-skilled and insufficiently motivated human resource in terms of salary. At the same time, the seaside tourism in Romania is characterized by an accentuated seasonality, which generates great problems for the providers of tourist services in this area.